Solvent‐Mediated Structural Evolution in Colloidal Lead Halide Perovskite Nanocrystals Self‐Assembly. Issue 19 (29th May 2022) - Chen, Linqi; Hu, Yingjie; Zhou, Beier; Dong, Hongxing; Mou, Nanli; He, Jin; Yang, Zhijie; Li, Jingzhou; Zhu, Zihao; Zhang, Long
Abstract: Figuring out the inner mechanism of lattice distortion and unstable factors of inorganic perovskite nanocrystals in solvents is essential for fundamental studies and applications in photonic devices. Traditional research results simply ascribed the unstable factor to solvent polarity, which in fact are insufficient and inaccurate to explain some phenomena. Here, we propose a molecular level mechanism that the crucial cause for the instability of perovskite nanocrystals in solutions is the competition between complex bond energies in colloidal nanocrystals system. In combination with molecular dynamics simulations and first principle calculations, the kinetic process of lattice distortion and self‐assembly of perovskite nanocrystals is revealed in solutions. By tailoring the relative magnitude of the hydrogen bond energy between ligand ammonium ion and halogen, the van der Waals force between the ligands of adjacent nanocrystals and the bond energy between lead atom and halogen, nanocrystal arrays and single‐crystalline nanowires based on all‐inorganic perovskite nanocrystals can be freely obtained. Moreover, the polarization properties of the obtained nanowires are studied, which are related to their formation process. Abstract : This work reports a molecular scale mechanism of solvent‐mediated evolution of inorganic perovskite nanocrystals (NCs). By affecting the intermolecular forces between aliphatic ligands on adjacent NCs and regulating the competition between complex bond energy in colloidal NCs system, solvent molecules can regulate the self‐assembly of ligand‐stabilized perovskite nanocrystals and then nanocrystal arrays and nanowires are freely obtained.